Turner syndrome transition clinic in the West of Scotland: a perspective - Zahra, Baryab; Sastry, Aparna; Freel, Marie; Donaldson, Malcolm; Mason, Avril (Frontiers in Endocrinology, 2023)
Turner Syndrome (TS) is the commonest chromosomal abnormality in females. Establishing and maintaining long-term follow-up after transition to adult endocrine services, to allow for essential lifelong surveillance of hypertension and cardiovascular disease, and optimal hormone replacement, remains a challenge. A TS transition clinic was established with the aim of supporting successful transfer and establishing long-term follow-up in adult endocrine services. Our objectives are to evaluate the success of our TS transition service primarily in achieving and maintaining follow-up after transfer to adult services and to assess the adequacy of health surveillance post-transition with a specific focus on cardiac monitoring and hormone replacement. A departmental database was used to identify young people whose care had transferred to adult endocrine services. An electronic case record was utilised to obtain clinic attendance and relevant clinical information on cardiovascular monitoring and hormone replacement therapy (HRT). Forty-six (n=46) young people transferred to adult endocrine services during the observed 20-year period, 1998-2017. Thirty-six (n=36) had transferred prior to 2015, of whom sixteen (n=16, 44%) are lost to long-term follow-up at 5 years. Overall, 41 (89%) patients have had cardiac imaging surveillance since transferring, However, only 30 (73%) of these were carried out at the recommended frequencies. All 20 women in established follow-up have had cardiac imaging. Five out of the 46 (11%) patients do not have any documented cardiovascular monitoring. Forty (86.9%) women have had a documented BP measurement. Nineteen of the 20 women who are in 5-year established follow-up have a documented blood pressure. Five (11%) women are not on HRT, while two (4%) remain on oestrogen-only HRT. Thirty-seven (80.4%) women are on combined HRT, only eight (21.6%) are on the recommended form of oestradiol. Two (4%) are not on HRT due to normal ovarian function. A significant proportion of girls with TS are currently lost to adult endocrine services. Strategies to improve long-term endocrine follow-up are needed to ensure lifelong health needs and adequate hormone replacement are met. Whilst similar parameters are monitored in adult endocrine services a group of patients may be at risk of receiving inadequate HRT and developing cardiovascular complications.